Perdido en el paraíso - Nooteboom, Cees, 1933-; Lorda Vidal, Isabel-Clara; Nooteboom, Cees, 1933- (Madrid : Ediciones Siruela, 2014)
Alma, a young Brazilian women recovering from a traumatic and brutal attack, sets out from Sao Paulo and winds up in Australia, where Dutch novelist Erik Zontag, in Perth for a literary conference, stumbles upon a winged woman curled up in a closet in an empty house.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Masseurs -- Fiction; Critics -- Fiction; Australia -- Fiction; Alps, Austrian (Austria) -- Fiction; Angels -- Fiction; Psychological fiction; Electronic books